Minimal access surgery in children: An initial experience of 28 months - Gupta Abhaya; Gupta Rahul; Jadhav Vinay; Sanghvi Beejal; Shah Hemanshi; Parelkar S (Wolters Kluwer Medknow Publications, 2009)
Background : This study reports our 28 months experience with minimal access surgery (MAS) in children. Materials and Methods : This was a review of all children who underwent MAS between December 2004 and March 2007 at the Departments of Paediatric Surgery, Seth Gordhandas Sunderdas Medical College (GSMC) and King Edward the VII Memorial (KEM) Hospital, India. Results and observations were tabulated and analysed, comparing with observations by various other authors regarding variety of indications such as, operative time, hospital stay, conversion rate, complications, safety, and feasibilty of MAS in neonates, in the appropriate operative groups. Results : A total of 199 procedures were performed in 193 children aged between 10 days and 12 years (average age: 5.7 years). One case of each, adrenal mass, retroperitoneoscopic nephrectomy, laparoscopic congenital diaphragmatic hernia (CDH) repair, and abdominoperineal pull-through for anorectal malformation, were converted to open surgeries due to technical difficulty. The overall conversion rate was 3%. Morbidity and mortality were very minimal and the procedures were well tolerated in majority of cases. Conclusion : We concluded that MAS procedures appear to be safe for a wide range of indications in neonates and children. Further development and expansion of its indications in neonatal and paediatric surgery requires further multi-institutional studies and larger cohort of patients, to compare with standards of open surgery.